2014
DOI: 10.1371/journal.pone.0087326
|View full text |Cite
|
Sign up to set email alerts
|

Design and Optimization of PLGA-Based Diclofenac Loaded Nanoparticles

Abstract: Drug based nanoparticle (NP) formulations have gained considerable attention over the past decade for their use in various drug formulations. NPs have been shown to increase bioavailability, decrease side effects of highly toxic drugs, and prolong drug release. Nonsteroidal anti-inflammatory drugs such as diclofenac block cyclooxygenase expression and reduce prostaglandin synthesis, which can lead to several side effects such as gastrointestinal bleeding and renal insufficiency. The aim of this study was to fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 41 publications
3
44
0
2
Order By: Relevance
“…However, it has been observed that the size of the nanoparticles was higher than that of the blank nanoparticles. This phenomenon has also been observed in a previous study [15].…”
Section: Discussionsupporting
confidence: 90%
“…However, it has been observed that the size of the nanoparticles was higher than that of the blank nanoparticles. This phenomenon has also been observed in a previous study [15].…”
Section: Discussionsupporting
confidence: 90%
“…It is, thus, reckoned that this fact can result on different adsorption efficiency of T-80. Moreover, although different surfactants (DMAB or DDAB) did not influence NPs physical properties, it is believed that due to the greater lipophilicity of DMAB, this surfactant can promote a better emulsification process for the formation of the polymeric condensate [41]. We could only verify small tendencies of improved PDI and ζ potential for this surfactant group.…”
Section: Discussionmentioning
confidence: 80%
“…They decreased the surface tension between the organic and aqueous phase that would stabilize an emulsion as well as solubilize the waterinsoluble drug. 2 Thus, an increase in their concentration in the aqueous phase would allow the diffusion and solubilization of more drugs out of the hydrophobic core into the external aqueous phase.…”
Section: Entrapment Efficiencymentioning
confidence: 99%
“…P188/0.2 and CA25/0.2, which are stabilizers with emulsifying properties, can form molecular micelles through the interaction between their hydrophobic portion and the hydrophobic polymer, which could highly affect the release of drug from the formed NPs, in different patterns for both P188 and CA25, possessing different surface activities. 2 Drug release data were fitted into various kinetics equations, namely zero-order, first-order, Higuchi, Korsmeyer-Peppas, Hixson-Crowell, Baker-Lonsdale, and …”
Section: In Vitro Release Studymentioning
confidence: 99%